Incidence Of Carbapenem Resistant Pseudomonas Aeruginosa Isolated From Patients With Lower Respiratory Tract Infection In Intesive Care Units (International Journal of Scientific Research and Management (IJSRM), 2015)
Carbapenems are used for treating serious infections caused by multidrug resistant gram negative bacilli including non-fermenters (NFGNB). The study documents the occurrence of carbapenem resistance in NFGNB Isolates obtained from patients with respiratory infection in the intensive care units (ICUs). Microbiological work was done of 720 respiratory specimensyielded 690 gram negative bacilli. This included,Klebsiella (150), Enterobactter (90), Escherichia Coli (120), Proteus Species (24), Citrobacter (20), Aeromonas (06), Pseudomonasaeruginosa (120) ,Achromobacter spp(95), Acinetobacter spp(65).This included NFGNB (280 ) , 46(16.4%) of 280 NFGNB were found to be resistant to imipenem & meropenem. Expectedly, Pseudomonas aeruginosa was the predominant NFGNB showing carbapenem resistance in 29 isolates(10.3%), 10 (3.5%) were Acinetobacter species and 7 (2.5%) were other NFGNB. 40 of these 46 NFGNB showed resistance to the other antibiotics tested. This study conducted at an Apollo Hospitals inrural region of Chhattisgarh State during January, 2014 to January 2015. The rapid dissemination of carbapenem is therapeutically challenging and necessitates effectiveantibiotics policies and meticulous surveillance program in critical care setting.